Social Capital in Forest Management of Gunung Sahilan Village Kampar District Riau Province - Mayarni Mayarni; Sujianto Sujianto (Iapa Proceedings Conference, 2019)
The Village Forest of Kenegerian Gunung Sahilan is one of the village forests that has been granted forest management permits by the Ministry of Environment and Forestry of the Republic of Indonesia in 2017. Management rights are given to Lembaga Pengelola Hutan Desa (LPHD) Kenegerian Gunung Sahilan which was represented by a traditional institution (ninik mamak). The institutional role has a considerable influence in the process of managing village forests so that social capital is needed. Social capital has a role as strengthening ties, relationships and networks among various institutions and social groups involved in village forest management policies.The purpose of this study was to analyze the formation of social capital in LPHD Kenegerian Gunung Sahilan. The method used in this study is aexplorative descriptive with a qualitative approach.The results of the study showed that at LPHD Gunung Sahilan had not applied the concept of social capital in village forest management activities optimally as evidenced by the lack of coordination between implementing actors, lack of community involvement and various activities dominated by certain groups. This causes the complexity and dynamics that are still very complicated, especially in social and economic aspects.